Application of cinnamon bark emulsions to protect strawberry jam from fungi. (May 2017) - Ribes, Susana; Fuentes, Ana; Talens, Pau; Barat, Jose Manuel
Abstract: The objective of the work was to evaluate the use of cinnamon bark-xanthan gum emulsions to preserve strawberry jam. The optimisation of the methodology used to prepare the emulsions and, the evaluation of their antimicrobial activity in culture media and in the strawberry jam were investigated. Emulsions were prepared in either a rotor-stator homogeniser or a magnetic stirrer combined with a high pressure homogeniser. Microorganism suspensions (10 3 and 10 6 CFU/mL), essential oil concentration and microbial sensitivity were decisive in the emulsions' antimicrobial activity. The high stress applied to samples and their heating during homogenisation caused essential oil content losses. The jams prepared with the oil-in-water emulsions inoculated with Aspergillus flavus, Penicillium expansum, Zygosaccharomyces rouxii and Zygosaccharomyces bailii exhibited no growth during the 28 days of analysis The obtained results indicated the suitability of cinnamon bark oil-xanthan gum emulsions for preserving strawberry jam. Highlights: Antimicrobial oil-in-water emulsions containing cinnamon bark oil were studied. The methodology used to prepare oil-in-water emulsions was optimized. Fungi suspensions had an important role in the cinnamon bark oil activity. The homogenisation process increased trans-cinnamaldehyde losses. Cinnamon bark oil emulsions were able to prevent fungi growth in strawberry jam.